Pengaruh Komitmen Afektif dan Work Related Stress terhadap Auditor Turnover Intention - Utama, Fikri Rizki; Rohman, Fatkhur (Budgeting: Jurnal Akuntansi Syariah, 2025)
Human Resources (HR) play a crucial role in the sustainable development of a company. Public Accounting Firm (KAP) partners need to maintain turnover intentions to enhance auditor staff loyalty. The purpose of this study was to obtain empirical evidence on the influence of affective commitment and work-related stress on auditor turnover intention. The research method employed a survey. The convenience sampling method was chosen for the sampling technique, with the criteria being public accountants working at KAPs in Bandar Lampung City. The data used in this study were primary data collected through questionnaires. The Smart-PLS version 3.3.9 was used to process the collected primary data. The results showed a significant negative effect of affective commitment on auditor turnover intention. However, work-related stress had no effect on auditor turnover intention. The two independent variables in this study explained 50.7% of the external auditor turnover intention phenomenon, emphasizing the importance of understanding the behavior of public accountants working at KAPs. Suggestions for further studies include expanding the scope of independent variables influencing auditor turnover intention, such as auditor performance or job satisfaction. Thus, the results of this study can be the initial foundation for more in-depth research related to auditor turnover intention.